Health education can save the environment from medicine residues - Giulia de Souza Castro; Estael Luzia Coelho da Cruz-Cazarim; Marcelo da Silva Silvério; Alessandra Ésther de Mendonça; Maurílio de Souza Cazarim (Brazilian Journal of Pharmaceutical Sciences, 2023)
Abstract The incorrect disposal of medicines and their environmental impact has been related to the health medicalization and the improper use of medication by society. In this sense, it is very important to know the profile of drug disposal for foster health policies. The aim was to identify the profile of disposal of medicines by the population, including the cost perspective. This is an inquiry descriptive study that began in September 2019. Medicine disposal health education program was carried out over six months in two University pharmacies. A questionnaire for sociodemographic and discarded medicines data collection was applied. Logistic regression analysis for variables association of correct disposal and the chi-square and t-student analysis for comparison between disposal programs were performed for a level of 5% and test power of 80%. Medicines weighed 23.3 kg and 28.5 kg, with the cost variation from US$ 13.5 to US$ 16.1 until the final treatment. The correct disposal was strongly associated with the disposal reason (p=0.013), source of information (p=0.006), prescription (p=0.03), form of use (p=0.01), acquisition source (p=0.001), cost with medication (p=0.0001), education (p=0.028) and age (p=0.05). The correct medicine disposal was associated with important features of the community related to education health.